INVESTIGATING EFL STUDENTS’ PERCEPTION IN READING COMPREHENSION THROUGH GOOGLE CLASSROOM - Faizah, Maftuhatul; Mustofa, Mutmainnah; Hasanah, Nur; Dzulfikri, Dzulfikri; Rafiqi, Iqbal (Reflektika, 2021)
One of the most crucial language skills for students to achieve is reading. Through their participation in this activity, students can improve their language skills and get experience. Using Google Classroom, this study attempted to examine EFL students' perceptions of reading comprehension. Because TBI (English Teaching Department) IAIN Madura is one of the universities that conducts online learning, it was chosen as the study's subject. This study used a sample of 26 students. Purposive sampling was used as a sample technique in this study. The results indicate that the students submitted useful and good responses. The results show that no student answered strongly disagree (SD), 3 students chose to disagree (11,5%), 16 students chose to agree (75%), and 6 students chose to strongly agree (23%). Google Classroom, it can be concluded, is a solution for online learning classes. As a result, Google Classroom can be used to collect student assignments and, more importantly, to help students improve their reading comprehension. Furthermore, if this application is effective, successful, and also assists students in assisting in e-learning, particularly in receiving feedback after completing the work assigned by the lecturer, it can be used in conjunction with Google Classroom as an e-learning solution for COVID-19.